Pro-social missions and worker motivation: An experimental study - Sebastian Fehrler; Michael Kosfeld (Institute for the Study of Labor (IZA), 2012)
Do employees work harder if their job has the right mission? In a laboratory labor market experiment, we test whether subjects provide higher effort if they can choose the mission of their job. We observe that subjects do not provide higher effort than in a control treatment. Surprised by this finding, we run a second experiment in which subjects can choose whether they want to work on a job with their preferred mission or not. A subgroup of agents (roughly one third) is willing to do so even if this option is more costly than choosing the alternative job. Moreover, we find that these subjects provide substantially higher effort. These results suggest that relatively few workers can be motivated by missions and that selection into mission-oriented organizations is important to explain empirical findings of lower wages and high motivation in the latter.
urn:nbn:de:101:1-201208065420
Keywords: C92; J33; M52; 330; motivation; effort provision; contract choice; sorting; lab experiment; Leistungsmotivation; Arbeitsleistung; Soziales Verhalten; Betriebswirtschaftliches Ziel; Test